Empowering Tahfiz students through integrated learning: an impact study of the ASSETS 2025 program - Affendy Lee, Noor Azli; Abd Rahman, Nor Hanim (Unit Penerbitan JSKM, 2025)
The ASSETS (Academic and Skills Enhancement Through Strategic Training) 2025 program aimed to integrate academic and practical skills into the Tahfiz education framework, which traditionally focuses on Quranic memorization. Held over three days from 24 to 26 April 2025, the program involved 23 male students aged 10 to 18 from Maahad Riyadhil Quran (MRIQ). It featured modules in both academic subjects (English and Computer-Mathematics) and practical skills (speed reading, archery, culinary arts, and public speaking). Using a pre- and post-program survey, the results showed strong improvements in practical domains: speed reading (69.6%), archery (65.2%), and culinary arts (60.9%). Academic progress was also evident in English (65.2%) and Computer-Mathematics (60.9%), suggesting better engagement strategies compared to the previous year. The study affirms the ASSETS model's effectiveness in promoting holistic student development, though continued refinement is needed for long-term skill retention and diversified implementation across other Tahfiz centers.